Use of social media for Climate Engagement and Awareness among the Young People in Kenya - Gaceri, Mary Asunta (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Climate change presents significant challenges to the global community, and Kenya is not exempt from its effects. The effects of climate change have significantly influenced the livelihoods of people worldwide in aspects encompassing health, agricultural practices, transportation, education, and beyond. This calls for innovative ways to address the challenges of climate change. Engaging and raising awareness among young people about climate change is essential due to their high energy levels and greater effectiveness in transmitting knowledge. This helps bridge the gap in climate change awareness, particularly among the rapidly growing younger generation who will become future decision-makers. Additionally, this contributes to the promotion of a sustainable future through efforts to address climate change. To effectively engage young people, we must align our approach with their behaviors. Mostly the youthful generation exhibits a way of living that involves a lot of interactive activities, notably through social media platforms. Given the increasing number of social media users and Kenya's ranking as the top country in East Africa for social media usage, it is crucial to recognize the significance of utilizing social media for climate change initiatives. This study investigates the use of social media for climate change engagement and awareness among young people in Kenya through the use of a structured questionnaire with respondents from diverse parts of Kenya. Some of the findings indicated that about 33.3% of respondents spend more than four hours daily on social media, while 36.7% reported that they rarely encounter any climate change content on the platforms. 80% of the respondents believe that social media can lead to real-world action on climate change. The study will be used to inform strategy on climate change action.